Analysis of Canva-Based OSN Mathematics Teaching Materials Design for Grade V Elementary School - Reni Sularsih (South Sulawesi Education Development (SSED), 2025)
This study focuses on the analysis of a Canva-based instructional Teaching Materials specifically designed for fifth-grade students preparing for the National Science Olympiad (OSN) in Mathematics. The primary aim is to create a resource that addresses the significant challenges identified in competitive mathematics education, including language barriers, technological access, and the need for differentiated instruction. The Teaching Materials integrates visual and interactive elements facilitated by Canva, enhancing student engagement and understanding of complex mathematical concepts. It also includes bilingual support and digital literacy components to ensure inclusivity for students from diverse linguistic and socioeconomic backgrounds. By leveraging the customizable features of Canva, the Teaching Materials provides a flexible and adaptive learning tool that can cater to varying levels of student proficiency and technological access. The study's findings suggest that such a resource not only improves student readiness for the OSN competition but also promotes educational equity by mitigating the impact of the digital divide and other systemic barriers. This research contributes to the broader discourse on digital education, offering insights into the effective integration of technology in the analysis of competitive academic resources. Future research is recommended to evaluate the long-term impact of these resources on student performance and to explore further enhancements in digital educational tools.